2014
DOI: 10.1177/1040638713519641
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Avian bornavirus in multiple tissues of infected psittacine birds using real-time reverse transcription polymerase chain reaction

Abstract: Avian bornavirus (ABV), the cause of proventricular dilation disease in psittacine birds, has been detected in multiple tissues of infected birds using immunohistochemical staining (IHC) and reverse transcription polymerase chain reaction (RT-PCR). In the current study, real-time RT-PCR, using primers targeting the ABV matrix gene, was used to detect ABV in 146 tissues from 7 ABV-infected psittacine birds. Eighty-six percent of the samples tested positive, with crossing point values ranging from 13.82 to 37.82… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 19 publications
(51 reference statements)
2
15
0
2
Order By: Relevance
“…Intestine, lung and whole blood from this bird were positive by RT-PCR, whereas the liver tested negative. This is in congruence with the detection of comparably low viral loads in the livers of bornavirus-infected psittacines [ 5 , 42 ].…”
Section: Resultssupporting
confidence: 81%
“…Intestine, lung and whole blood from this bird were positive by RT-PCR, whereas the liver tested negative. This is in congruence with the detection of comparably low viral loads in the livers of bornavirus-infected psittacines [ 5 , 42 ].…”
Section: Resultssupporting
confidence: 81%
“…The use of anti-bird IgY secondary antibody in the Western blot worked well for Blue and gold macaw, Cockatiel, and Mallard plasmas, a result similar to that obtained in other studies using anti-bird IgY secondary antibody to detect ABV exposure. 9,11,20 However using the anti-bird IgY secondary antibody in the dot-blot ELISA, the Blue and gold macaw and Cockatiel samples had poor positive responses while the Mallard samples were strongly positive. Monk parakeet plasma was not assayed by Western blotting due to the limited plasma volume available.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Sampling for histopathology and tissue immunoassays, especially of nervous tissues, is not practical in living birds, thus these tests are more commonly used in post-mortem diagnosis. Reverse transcriptase polymerase chain reaction (RT-PCR) can utilize less invasive samples such as feather follicles, feces/urine, and cloacal swabs, 5,7,[9][10][11][12][13] however sensitivity will vary due to intermittent viral shedding. [13][14][15] Immunologic testing comparing ABV specific antigens found that the viral nucleoprotein is immunodominant and hence the best antigen to use in a microtiter plate ELISA and in fluorescent antibody assays.…”
Section: Introductionmentioning
confidence: 99%
“…Bornavirussen zijn enkelstrengige RNA-virussen behorend tot de orde Mononegavirales waartoe eveneens het "borna disease virus" (BDV) behoort dat voornamelijk bij schapen, katten en paarden encefalitis veroorzaakt (Hoppes et al, 2010). ABV kan bij klinisch geïnfecteerde vogels in een groot aantal organen aangetroffen worden (Delnatte et al, 2014;Rinder et al, 2009); dit in tegenstelling tot BDV dat een tropisme voor het centrale en perifere zenuwstelsel vertoont (Berg et al, 2001;Ludwig et al, 1985;Malkinson et al, 1993). Er werden reeds 13 verschillende genotypes van het ABV aangetoond Honkavouri et al, 2008;Kistler et al, 2008;Rubbenstroth et al, 2012;.…”
Section: Inleidingunclassified
“…RT-PCR voor de detectie van ABV kan uitgevoerd worden op urofecale stalen, vederstalen en op bloed (Delnatte et al, 2014;. Alhoewel viremie bij KDS meestal pas optreedt wanneer de aandoening reeds vergevorderd is, zou het testen van bloedstalen volgens sommige auteurs een goede sensitiviteit hebben Hoppes et al, 2013).…”
Section: Rt-pcrunclassified